Exploring the effects of small- and medium-sized enterprise employees' job satisfaction on their innovative work behaviours: the moderating effects of personality. Issue 2 (29th April 2021) - Mustafa, Michael; Coetzer, Alan; Ramos, Hazel Melanie; Fuhrer, Jorg
Abstract : Purpose: The purpose is to contribute to the debate on how job satisfaction might influence small and medium-sized enterprise (SME) employees' propensity to engage in innovative work behaviours. The authors examine the relations between job satisfaction and innovative work behaviour and each of its sub-dimensions: idea generation, promotion and realisation. Additionally, the authors explore the potential moderating effects of openness to experience and conscientiousness on the relations between job satisfaction and innovative work behaviour and each of the sub-dimensions of innovative work behaviour. Design/methodology/approach: Paper-based questionnaires were used to collect data from employees in 28 SMEs located in the Aargau region of Switzerland. All the SMEs were part of the high-tech manufacturing industry. The authors' hypothesized model was tested using hierarchal regression analysis on a sample of 125 employees. Findings: Job satisfaction was positively related to innovative work behaviour and to each of its sub-dimensions: idea generation, promotion and realisation. Openness to experience moderated the relationships between job satisfaction and innovative work behaviour and job satisfaction and the sub-dimensions idea generation, idea promotion and idea realisation. However, conscientiousness did not moderate the relationship between job satisfaction and innovative work behaviour, nor between job satisfaction and each of the sub-dimensions of innovative work behaviour. Practical implications: Findings demonstrate that supportive work environments in SMEs which help develop job satisfaction among employees can have positive effects on the discretionary performances of employees. Originality/value: Studies that examine relationships between job satisfaction and innovative work behaviours in SMEs are extremely sparse. This study makes novel contributions to this line of inquiry by examining how job satisfaction relates to each of the three sub-dimensions of innovative work behaviour and by exploring the potential moderating roles of two important personality traits in these relationships.